(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Developing environmental awareness in children is essential for fostering a sustainable future. This thesis explores interactive methods such as experiential learning, technology integration, play-based strategies, and community involvement to enhance children’s ecological understanding. By engaging in hands-on activities, digital simulations, storytelling, and real-world environmental initiatives, children develop a lasting commitment to sustainability. Incorporating these interactive approaches into education ensures a deeper connection to nature and responsible environmental behavior.